Rhizosphere Microbial Communities and Heavy Metals - Barra Caracciolo, Anna (Microorganisms, 2021)
The rhizosphere is a microhabitat where there is an intense chemical dialogue between plants and microorganisms. The two coexist and develop synergistic actions, which can promote plants’ functions and productivity, but also their capacity to respond to stress conditions, including heavy metal (HM) contamination. If HMs are present in soils used for agriculture, there is a risk of metal uptake by edible plants with subsequent bioaccumulation in humans and animals and detrimental consequences for their health. Plant productivity can also be negatively affected. Many bacteria have defensive mechanisms for resisting heavy metals and, through various complex processes, can improve plant response to HM stress. Bacteria-plant synergic interactions in the rhizosphere, as a homeostatic ecosystem response to HM disturbance, are common in soil. However, this is hard to achieve in agroecosystems managed with traditional practices, because concentrating on maximizing crop yield does not make it possible to establish rhizosphere interactions. Improving knowledge of the complex interactions mediated by plant exudates and secondary metabolites can lead to nature-based solutions for plant health in HM contaminated soils. This paper reports the main ecotoxicological effects of HMs and the various compounds (including several secondary metabolites) produced by plant-microorganism holobionts for removing, immobilizing and containing toxic elements.